A note on separation by subadditive and sublinear functions - Nikodem, Kazimierz; Sadowska, Elżbieta; Wąsowicz, Szymon (Annales Mathematicae Silesianae, 2022)
The necessary and sufficient conditions for separation by subadditive and sublinear functions are given.